(untitled) (AYUSHDHARA, 2024)
Abstract: Alopecia areata, or Indralupt in Ayurveda, is a dermatological condition characterized by localized, non-scarring hair loss. It presents as circular or oval patches of baldness, primarily affecting the scalp. While its exact cause remains unclear, autoimmune factors are thought to play a significant role. Management typically involves a combination of topical and systemic treatments, including corticosteroids and immunomodulators which is not fully preventive or curative. Thus, Vata, Pitta, and Kapha Dosha i.e., Tridosha and Rakta Dushya are the causative factors of Indralupta. Materials and Method: Cup, Cupping pump, cotton ball or Swab, antiseptic solution, sterile lancets or scalpel, gloves. The patient was scheduled for wet cupping therapy, with a seven-day interval between each of the three sessions. Significant hair growth was observed after just one session. Raktamokshan, particularly Prachchanna (blood-letting, primarily scraping) is beneficial for removing vitiated Rakta if it is located in a specific area of the body, such as hair follicles. Result : After undergoing Wet Cupping and internal Rasayan drug for duration of one month, two patches of hair loss affected by alopecia areata were completely removed. Conclusion: This case report investigates the effectiveness of Raktmokshan, a traditional Ayurvedic therapy involving wet cupping, and Rasayan chikitsa in the management of alopecia areata (Indralupt). The case presents a patient with alopecia areata who underwent Raktmokshan therapy and observed outcomes over a defined period.